ASEAN Territorial Trading Liberalization through ASEAN Charter Retification for Indonesia under the Legal Aspect Review - Jhon, M.; Delfiyanti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Andalas, 2021)
ASEAN Charter is the most important “legal instrument” and sucessor of Bangkok Declaration 1967. It also contain the status and position of ASEAN on the including agreement. The Charter come into effect since 15 December 2008 after ratification of ten ASEAN member-states. Indonesia was ratifying by Act No.38 of 2008 on ratification of ASEAN Charter. It had a legally binding to Indonesia. The content related to the establishment of ASEAN Economic Community in economy, socioculture, and security politics. Moreover, the agreement comprise a critical issue, trading liberalization or “ASEAN Single Market” through ASEAN Economic Community. Therefore, the ratification of ASEAN Charter gives significant influence to the Indonesia in the future. By the reasons, the objectives of research are, first, analyze the implication of Act No.38 of 2008 on ratification of ASEAN Charter to Indonesia in correlation with ASEAN Economic Community under legal aspect review, and second, analyze the challenge and opportunity in participation of ASEAN Economic Community as indonesia has ratified the Charter.